Pengaruh Pemberian Ekstrak Etanol Buah Naga Putih (Hylocereus undatus) terhadap Kerusakan Histologis Sel Hepar Mencit (Mus musculus) yang Diinduksi Parasetamol - Kurniawan, Ardelia; ., Muthmainah; Murti, Bhisma (Nexus Biomedika, 2012)
Background: Antioxidants in white dragon fruit are vitamin A, C, E, and polyphenol which are estimated having hepatoprotective function. The purpose of this research is to know the effect of ethanol extract of white dragon fruit (Hylocereus undatus) to the histological damage of the hepar cells of mice (Mus musculus) induced by paracetamol. Methods : This research was Randomized Controlled Trial design with sample of 28 Swiss Webster mice, male, 2-3 months old, and ±20 grams of weight each. The sample was divided into 4 groups by randomization. The control group (KK) and the treatment group 1 (KP1) were fed aquadest orally 0,3 ml/20 g body weight a day for 14 days. The treatment group 2 (KP2 ) and 3 (KP3) were fed 70 and 140 mg/20 g body weight the extract of white dragon fruit a day for 14 days. On the 12th to 14th days, mice of KP1, KP2, and KP3 were treated by 5,07 mg paracetamol per 20 g body weight. On the 15th day, hepars of mice were taken and stainned with HE for histopathological study. The hepar cells of mice were observed microscopically by counting the number of necrosis cells on the centrolobuler zone. The data were analyzed by Oneway ANOVA test and Post Hoc test. Results: The average damage of hepar cells in the KK, KP1, KP2, KP3 was 21,79±2,69; 63,79±6,41; 32,07±2,97; 19,36±1,91 consecutively. The results of Oneway ANOVA test showed a significant difference in all group (p<0.001). The results of Post Hoc test showed significant differences between KK-KP1, KK-KP2, KP1-KP2, KP1-KP3, KP2-KP3 with p<0.001, except KK-KP3 with p=0.06. Conclusions : The ethanol extract of white dragon fruit (Hylocereus undatus) can prevent the histological damage of the hepar cells of mice (Mus musculus) induced by paracetamol. Keywords : ethanol extract of white dragon fruit, paracetamol, damage of hepar cells